Prognostic association of plasma NT-proBNP levels in patients with microvascular angina -A report from the international cohort study by COVADIS-. (December 2022) - Suda, Akira; Takahashi, Jun; Schwidder, Maike; Ong, Peter; Ang, Daniel; Berry, Colin; Camici, Paolo G.; Crea, Filippo; Carlos Kaski, Juan; Pepine, Carl; Rimoldi, Ornella; Sechtem, Udo; et al.
Highlights: Plasma NT-proBNP levels may be a new prognostic biomarker of microvascular angina. Abstract: Backgroud The aim of this study was to assess the prognostic association of plasma levels of N -terminal prohormone of brain natriuretic peptide (NT-proBNP) with clinical outcomes of patients with microvascular angina (MVA). Methods: In this international prospective cohort study of MVA by the Coronary Vasomotor Disorders International Study (COVADIS) group, we examined the association between plasma NT-proBNP levels and the incidence of major adverse cardiovascular events (MACE), including cardiovascular death, non-fatal myocardial infarction, non-fatal stroke, and hospitalization due to heart failure or unstable angina. Results: We examined a total of 226 MVA patients (M/F 66/160, 61.9 ± 10.2 [SD] yrs.) with both plasma NT-proBNP levels and echocardiography data available at the time of enrolment. The median level of NT-proBNP level was 94 pg/ml, while mean left ventricular ejection fraction was 69.2 ± 10.9 % and E/e' 10.7 ± 5.2. During follow-up period of a median of 365 days (IQR 365–482), 29 MACEs occurred. Receiver-operating characteristics curve analysis identified plasma NT-proBNP level of 78 pg/ml as the optimal cut-off value. Multivariable logistic regression analysis revealed that plasma NT-proBNP level ≥ 78 pg/ml significantly correlated with the incidence of MACE (odds ratio (OR) [95 % confidence interval (CI)] 3.11[1.14–8.49], P = 0.001). Accordingly, Kaplan-Meier survival analysis showed a significantly worse prognosis in the group with NT-proBNP ≥ 78 (log-rank test, P < 0.03). Finally, a significant positive correlation was observed between plasma NT-proBNP levels and E/e' (R = 0.445, P < 0.0001). Conclusions: These results indicate that plasma NT-proBNP levels may represent a novel prognostic biomarker for MVA patients.